Diversifikasi Kebutuhan Ternak Ruminansia Melalui Budidaya Rusa Sambar (Cervus unicolor): Tinjauan Aspek Fisiologis - Maksudi, Maksudi; Lukman, Haris; Rahayu, Pudji (Fakultas Peternakan Universitas Jambi, 2010)
The research was conducted to evaluate the effects of domestication of Sambar deer (Cervus unicolor) on performance and hematological values. One captive Sambar deer was housed in an individual cages fitted on a slatted floor of 2 x 3 m2 . The diet was consisted of field grasses, legume and forages given ad libitum and sweat potatoes. The data were collected during a two-month period following a one-month adaptation period; The feed and the residues were collected daily, and the blood samples for hematological values were collected via jugular vein. The data were obtained three times; at the beginning (0 month), in the middle (1 month), and in the end (2 months) of the trial. The performance results showed that BW in the three respective times were 12.17, 15.60 and 19.40 kg; ADG in the first and the second month respectively ware 115 dan 127 gr/d; Total of DM consumption were 987 and 1216 gr/d; and the percentage of DM/BW were 6,33 dan 6,27%. The following averages of hematological values were obtained: erythrocytes 8,4, 7,9 dan 7,9 million/ml; Hemoglobin 11,4, 11,2 and 13,2 gr/100 ml; PCV 0,62, 0,57 and 0.50%; Leukosytes 14750, 11547 and 9721/ml; pH 7,34, 7,45 and 7,40, respectively. Finally, Sambar deer as the wild animals have prospective values when they are domesticated and intensively cared.